Evaluation of cytotoxicity, genotoxicity and ecotoxicity of nanoemulsions containing Mancozeb and Eugenol - da Silva Gundel S. (2019)
© 2018 Elsevier Inc.Mancozeb is a fungicide widely used in agriculture, mostly against the pathogen Glomerella cingulata responsible for the rot of ripe grape, but presents high toxicity. Strategies are sought to reduce the toxicity of this fungicide and alternative treatments are welcome. An alternative could be the use of clove oil, which has Eugenol as its major compound, and has antifungal potential against G. cingulata, however, Eugenol is susceptible to degradation processes which may compromise its efficacy. The nanoencapsulation of Mancozeb and Eugenol is a possible strategy to overcome the limitations of toxicity, solubility and instability of these compounds. Therefore, the objective of this study is to develop nanoemulsions containing Mancozeb (0.1 mg/mL) and Eugenol (33 mg/mL), isolated or associated, and evaluate the safety of these formulations through cytotoxicity, genotoxicity and ecotoxicity tests. Nanoemulsions were developed by the spontaneous emulsification method, cytotoxicity and genotoxicity were evaluated in healthy human cells through MTT, Dichlorofluorescein diacetate and Picogreen tests, and ecotoxicity assessment was carried out using the chronic toxicity test in springtails. After preparation, the physicochemical characterization of the nanoemulsions were performed which presented mean particle size between 200 and 300 nm, polydispersity index less than 0.3, negative zeta potential and acid pH. The nanoencapsulation was able to avoid the reduction of the cell viability caused by Mancozeb, while Eugenol was shown to be safe for cell use in both free and nanostructured forms, however the association of the two active compounds showed toxicity in the higher doses of Mancozeb. In the ecotoxicity tests, both free Mancozeb and Eugenol forms presented high toxic potential for soil, whereas the nanoencapsulation of these compounds did not cause a reduction in number of springtails. Therefore, from the tests performed, it was possible to observe that nanoencapsulation of Mancozeb and Eugenol is a safe alternative for the application of these compounds mainly in agriculture.